2012
DOI: 10.1142/s1793431112500170
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Containment Walls for Liquefaction Remediation

Abstract: Many typical ground improvement techniques that are used for liquefaction remediation, such as in situ densification, are not appropriate for application under existing buildings and more novel techniques are required. This paper describes centrifuge tests investigating the performance of rigid containment walls as a liquefaction remediation method. A simple frame structure, founded on a deep layer of loose, liquefiable sand was tested under earthquake shaking. Centrifuge tests were then carried out with conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The evaluation of the foundation dynamic response concluded that positive results with respect to settlement reduction are possible. Moreover, Mitrani and Madabhushi (2012) performed centrifuge tests to study containment walls proving their effectiveness in settlement minimisation and the relevance of the wall permeability as an important parameter. Dashti et al (2010a, b) performed centrifuge tests to analyse the better understanding of settlement mechanisms during earthquakes by using structural walls and water impermeable barrier as mitigation techniques.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The evaluation of the foundation dynamic response concluded that positive results with respect to settlement reduction are possible. Moreover, Mitrani and Madabhushi (2012) performed centrifuge tests to study containment walls proving their effectiveness in settlement minimisation and the relevance of the wall permeability as an important parameter. Dashti et al (2010a, b) performed centrifuge tests to analyse the better understanding of settlement mechanisms during earthquakes by using structural walls and water impermeable barrier as mitigation techniques.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Among the investigated techniques, they considered a sheet-pile enclosure. More recently, [12] investigated, by centrifuge testing, the performance of rigid containment walls as a liquefaction remediation method. Additionally, they observed that liquefaction within the contained foundation creates a base isolation mechanism reducing dynamic shear excitation.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, in order to prevent the damage effects of earthquake induced liquefaction in engineering structures, the countermeasure methods such as gravel drains, soil densification, solidification and inclusions or confinement walls among others are used. Such methods are studied by several authors via centrifuge tests (Liu and Dobry 1997;Adalier et al 1998;Brennan and Madabhushi 2002;Elgamal et al 2002;Dashti et al 2010b;Mitrani and Madabhushi 2012) or numerically (Elgamal et al 2002;Elgamal et al 2005;López-Querol and Blázquez 2006;Nishimura and Shimizu 2008;Lu et al 2011;Bradley et al 2013; Lopez-Caballero and Modaressi-Farahmand-Razavi 2013;Xu et al 2013). The principal conclusion of these works is that the efficiency of each solution depends on characteristics of the input signal and the properties of the soil.…”
mentioning
confidence: 99%